2017
DOI: 10.1002/jmri.25713
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal evaluation of perfusion changes in acute and chronic renal allograft rejection using arterial spin labeling in translational mouse models

Abstract: 2 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2017;46:1664-1672.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 32 publications
(42 reference statements)
2
15
0
Order By: Relevance
“…After slice‐selective and global inversion, images were acquired in free breathing in the coronal plane with the following parameters: repetition time (TR)/echo time (TE) = 4.0/2.0 ms, inversion time = 1200 ms, field of view (FOV) = 420 × 420 mm 2 , matrix = 128 × 128, slice thickness = 5 mm, averages = 30 and acquisition time = 4 min. Following motion correction of ASL images with elastic registration, maps of renal perfusion were calculated using MATLAB software (MathWorks, Natick, MA, USA) . Mean cortical perfusion values were determined by two independent readers, both blinded to results of blood values and type of pharmacological intervention, by using regions of interest (ROIs).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After slice‐selective and global inversion, images were acquired in free breathing in the coronal plane with the following parameters: repetition time (TR)/echo time (TE) = 4.0/2.0 ms, inversion time = 1200 ms, field of view (FOV) = 420 × 420 mm 2 , matrix = 128 × 128, slice thickness = 5 mm, averages = 30 and acquisition time = 4 min. Following motion correction of ASL images with elastic registration, maps of renal perfusion were calculated using MATLAB software (MathWorks, Natick, MA, USA) . Mean cortical perfusion values were determined by two independent readers, both blinded to results of blood values and type of pharmacological intervention, by using regions of interest (ROIs).…”
Section: Methodsmentioning
confidence: 99%
“…Following motion correction of ASL images with elastic registration, maps of renal perfusion were calculated using MATLAB software (MathWorks, Natick, MA, USA). [20] Mean cortical perfusion values were determined by two independent readers, both blinded to results of blood values and type of pharmacological intervention, by using regions of interest (ROIs). ROIs were placed into the upper, middle and lower third of the renal cortex, and mean cortical perfusion of both kidneys was calculated.…”
Section: Mri Protocol and Image Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It may well be that the increased expression of C5aR1, C5aR2, and C3aR observed in this study are secondary effects of heme-mediated complement activation. Further studies are required to elucidate the interplay of labile heme and anaphylatoxin receptors by using genetically modified mouse models in renal IRI and kidney transplantation (36,40). Heme has also been proposed to be a danger associated molecular pattern (DAMP) (41) that can amplify TLR4 signaling.…”
Section: Underlying Mechanisms Of Heme-mediated Inflammation After Irimentioning
confidence: 99%
“…Development of imaging techniques for graft evaluation and follow-up could contribute to a more reliable graft assessment. Several studies from the research group of Hueper et al, using a kidney transplantation animal model, have shown promising results for the use of MR after transplantation [16][17][18][19]. This same research group and several others have initiated studies to translate these outcomes to the clinical setting, showing significant associations between renal allograft function and several MRI sequences in small and heterogeneous cohorts [20][21][22][23][24].…”
Section: Lessons Learntmentioning
confidence: 99%